PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KOPI BUBUK ORIGINAL SAHABAT DI UKM KOPI SAHABAT LUBUKLINGGAU - Asshiddiqy, Muhammad Hasby; Supriyanto, Supriyanto; Nisusmiati, Murlina (Jurnal Media Ekonomi (JURMEK), 2021)
The problem in this research is that your ground coffee is still unable to compete with other brands of ground coffee and that your friend's ground coffee is still lacking in observing post-purchase behavior on consumers. This study uses observation data collection methods, distributing questionnaires, and conducting documentation to find data. This study shows that there is an influence of price and promotion on purchasing decisions. The results of this study indicate that the variable Price (X1) on Purchase Decision (Y) shows the value of tcount = 2,952 which is greater than the value of ttable (1,689) with a sig level. = 0.05. This means that it can be concluded that at UKM Kopi Sahabat, Lubuklinggau City. Promotion variable (X2) on Purchase Decision (Y) shows the value of tcount = 2.075 is greater than the value of ttable = (1.689) with a sig level. = 0.05. This means that it can be concluded that the promotion partially affects the purchasing decisions of the UKM Kopi Powder Sahabat Lubuklinggau. Based on the test results, the Fcount value obtained is 5.293 > Ftable = 3.27 and the simultaneous significance level of sig F is 0.010. It can be concluded that together (simultaneously) the independent variables of the study (Price and Promotion) have a significant effect on the dependent variable (Purchase Decision).